Teaching or Facilitating: A False Dichotomy* - Stewart, Douglas (Canadian Journal of Education/Revue canadienne de l’éducation, 1993)
A recent trend suggests teachers should facilitate learning rather than instruct children. This alarming idea is couched in the slogan “we facilitate learning, we don’t teach.” I argue that to take the idea seriously is to eclipse the tradition of teaching and push it to one side, putting at risk the general education of youngsters. I clarify the terms “teaching” and “facilitating,” and give reasons why the former, not the latter, should be emphasized. Une tendance récente suggère que les enseignants devraient faciliter l’apprentissage plutôt que d’enseigner. L’auteur soutient qu’en retenant cette idée inquiétante, on balaie du revers de la main toute une tradition de l’enseignement et on met en péril l’éducation générale des jeunes. L’auteur clarifie les deux approches et explique pourquoi la première, à savoir l’enseignement, devrait être privilégiée.